Celebrating downward mobility in selected Australian texts - Rubik, Margarete (Acta neophilologica, 2016)
Several critics have pointed out that the new lower class national hero from late 19th century onwards was invariably male, and that women were largely excluded from this national stereotype. Yet several recent Australian authors have portrayed female characters who correspond to this insubordinate, defiantly lower class ideal, and thereby insert women into the national myth.
Keywords: Australian fiction; Australian literature; avstralska književnost; avstralska proza; Bail, Murray; Grenville, Kate; Jefferis, Barbara; Lawrence, D. H.